2022
DOI: 10.3390/ijms23137321
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics and Reactive Nitrogen Species in Bacteria

Abstract: The production of reactive nitrogen species (RNS) by the innate immune system is part of the host's defense against invading pathogenic bacteria. In this review, we summarize recent studies on the molecular basis of the effects of nitric oxide and peroxynitrite on microbial respiration and energy conservation. We discuss possible molecular mechanisms underlying RNS resistance in bacteria mediated by unique respiratory oxygen reductases, the mycobacterial bcc-aa3 supercomplex, and bd-type cytochromes. A complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 171 publications
0
4
0
Order By: Relevance
“…However, cyt bc 1 -aa 3 is not essential for cell survival and as long as the alternate cyt bd is expressed, bc 1 -aa 3 inhibitors do not induce bactericidal effects. The central role of the bc 1 -aa 3 complex in the ETC and the significant differences to the mammalian counterpart make the supercomplex a good therapeutical target [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Emerging Mtb Drug Targetsmentioning
confidence: 99%
“…However, cyt bc 1 -aa 3 is not essential for cell survival and as long as the alternate cyt bd is expressed, bc 1 -aa 3 inhibitors do not induce bactericidal effects. The central role of the bc 1 -aa 3 complex in the ETC and the significant differences to the mammalian counterpart make the supercomplex a good therapeutical target [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Emerging Mtb Drug Targetsmentioning
confidence: 99%
“…NO is a diatomic free radical that is produced by the host immune system in response to bacterial infection. Exposure to NO and its congeners is both bactericidal and bacteriostatic, the effects being mediated through a range of well-known mechanisms, including modification of iron sulphur clusters [ 2 ], nitrosylation of thiol groups [ 3 ], nitration of tyrosine residues in the presence of superoxide [ 4 ], and through the inhibition of aerobic respiration via binding to haem cofactors of oxygen-dependent terminal oxidoreductases [ 5 ]. Bacteria can produce a variety of responses to NO [ 6 ], including systems involved in NO-detoxification, iron-sulphur (Fe-S) cluster repair, and the synthesis of NO-tolerant respiratory complexes such as cytochrome bd .…”
Section: No Is An Antimicrobial Respiratory Inhibitormentioning
confidence: 99%
“…A large body of evidence has demonstrated that bd -type oxidases, in addition to sustaining cell bioenergetics, can support virulence in several pathogens by providing protection against several stressors [ 25 ], including antibiotics [ 25 , 34 , 35 ], peroxynitrite [ 36 , 37 ], NO [ 38 , 39 ], hydrogen peroxide (H 2 O 2 ) [ 40 , 41 , 42 ], reactive oxygen species produced by macrophages, and H 2 S [ 43 ]. Significant sulfate concentrations and high H 2 S production have recently been reported in CF individuals infected by P. aeruginosa both at the site of infection and in the expectorate [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%